The recursive rule for a sequence is shown.

[tex]\[
\begin{array}{l}
a_n = a_{n-1} + 7 \\
a_1 = 17
\end{array}
\][/tex]

What is the explicit rule for this sequence?

A. [tex]\(a_n = 7n - 10\)[/tex]

B. [tex]\(a_n = 10n + 7\)[/tex]

C. [tex]\(a_n = 7n + 10\)[/tex]

D. [tex]\(a_n = 10n - 7\)[/tex]



Answer :

Let's start by understanding the given recursive rule for the sequence:

[tex]\[ a_n = a_{n-1} + 7 \quad \text{with} \quad a_1 = 17 \][/tex]

We need to find an explicit formula for [tex]\(a_n\)[/tex]. To do this, let's investigate the sequence for the first few terms:

- When [tex]\(n = 1\)[/tex]:
[tex]\[ a_1 = 17 \][/tex]

- When [tex]\(n = 2\)[/tex]:
[tex]\[ a_2 = a_1 + 7 = 17 + 7 = 24 \][/tex]

- When [tex]\(n = 3\)[/tex]:
[tex]\[ a_3 = a_2 + 7 = 24 + 7 = 31 \][/tex]

- When [tex]\(n = 4\)[/tex]:
[tex]\[ a_4 = a_3 + 7 = 31 + 7 = 38 \][/tex]

Now, let's observe a pattern and try to derive the explicit formula. Each term in the sequence can be seen as the initial term [tex]\(a_1\)[/tex], plus a multiple of 7:

[tex]\[ a_2 = 17 + 7 \cdot 1 \][/tex]
[tex]\[ a_3 = 17 + 7 \cdot 2 \][/tex]
[tex]\[ a_4 = 17 + 7 \cdot 3 \][/tex]

It appears that for the [tex]\(n\)[/tex]-th term:

[tex]\[ a_n = 17 + 7(n - 1) \][/tex]

We can simplify this expression to obtain the explicit formula:

[tex]\[ a_n = 17 + 7n - 7 \][/tex]
[tex]\[ a_n = 7n + 10 \][/tex]

Therefore, the correct choice for the explicit rule is:

[tex]\[ a_n = 7n + 10 \][/tex]

[tex]\(\boxed{a_n = 7n + 10}\)[/tex]